Therapeutic Potential of Sol-Gel ZnO Nanocrystals: Anticancer, Antioxidant, and Antimicrobial Tri-Action - Eren, Busra; Gunduz, Meliha Koldemir; Kaymak, Gullu; Berikten, Derya; Bahsi, Zehra Banu (Amer Chemical Soc, 2024)
Zinc oxide nanocrystals (ZnO NCs) hold great promise in nanomedicine with fascinating multifunctional properties. We investigated the therapeutic potential of sol-gel synthesized ZnO NCs with crystal sizes of 52.65 and 25.11 nm, focusing on their anticancer effects on HepG2 and HT29 cells, antioxidant properties, and antimicrobial activity. Both samples displayed a hexagonal wurtzite ZnO structure, wherein the crystal sizes diminished with lower calcination temperatures according to X-ray diffraction. The scanning electron microscopy analysis revealed that lowering the calcination temperature resulted in a decrease in the grain size of the ZnO NCs, as expected. This reduction in grain size combined with a decrease in crystal size resulted in a significant 40% reduction in the reflectance of the ZnO NCs in UV-vis-NIR spectroscopy. It was also observed that the ZnO NCs calcined at higher temperatures exhibited larger particle sizes with a reduced surface area mean of 69.30 mu m and a stable negative zeta potential of -11.2 mV. In contrast, the ZnO NCs calcined at lower temperatures exhibited a larger surface area mean of 34.56 mu m and a positive zeta potential of +10 mV. In both cell lines, the cytotoxic potential was found to be higher in HepG2 cells. Specifically, when ZnO nanocrystals (NCs) with a crystal size of 52.65 nm were used, the lowest cell viability was observed at a concentration of 5.74 mu g/mL. Based on oxidative stress index values, a lower crystal size of ZnO NCs displayed greater effectiveness in HT29 cells, while a higher crystal size of ZnO NCs had pronounced effects in HepG2 cells. Moreover, both ZnO NCs exhibited significant antimicrobial activity against Gram-positive bacteria (Enterococcus faecalis and Staphylococcus aureus) and Candida parapsilopsis fungus. These findings emphasize sol-gel ZnO NCs' potential as versatile agents in nanomedicine, spurring research on targeted cancer therapies and antimicrobial innovations.
Keywords: Zinc-Oxide Nanoparticles; Antibacterial Activity; Size